Rational medication use: a portuguese-angolan comparative study - Fernandes, Sara (2013)
Despite the information available about medication use, some risk behaviours persist, such as self-medication, poly-medication, non-adherence, and the disrespect for the health professional recommendations. Literature supports that informing people, through health education strategies alerting to risk behaviors, could promote a better use of medication.